Exploring the Renewable Energy Interventions Across the Globe: The Prospect & Progress of Solar Energy Ventures - Khan, Tahsina; Khanam, Shamsun Nahar (AIUB Journal of Business and Economics, 2019)
This qualitative study aims to explore the emergent renewable energy interventions across the globe from the perspective of recent solar energy applications to improve electrification scenario. Due to an ever-increasing demand for clean energy, rapid growth in the utilization of naturally available solar energy has been evident. Realizing the environmental implications and socio-economic development opportunities brought in by the growing adoption of renewables to meet the escalating electricity demand around the world, this study reviews and analyze the prevailing literature on solar electrification projects in selected developed and developing nations. To support this proposition, this article essentially consolidates the scholarly works and pertinent insights highlighting the progress and scope of solar energy programs in American, African, Asian and European nations to improve the electrification status and upgrade energy security. With this backdrop, this paper further highlights the current global trend on solar technology adoption to address energy efficiency and access to electricity for all, particularly to the underserved and underprivileged population.